Development and in vitro evaluation of pulsatile drug delivery system of enalapril maleate - Tosha, Sumaiya Mehjabin; Aziz, Ashima; Chisty, Sharmin Jahan; Asaduzzaman, Md; Bhuiyan, Mohiuddin Ahmed (Bangladesh Pharmaceutical Journal, 2015)
Pulsatile drug delivery of enalapril maleate is one such system that, by delivering drug at the right time, right place and in right amounts, holds good promises of benefit to the patients suffering from hypertension. The basic design involves the preparation of cross linked hard gelatin capsules using formaldehyde. Then the drug diluent mixtures were prepared and loaded which was separated by using hydrogel plug of polymers of different grades such as HPMC 50 cps, HPMC 100 cps, HPMC K4M, HPMC K15M, HPMC K100M, xanthan gum, carbopol 971 and sodium CMC at different amount (100 and 120 mg). Prepared formulations were subjected to evaluation of various physical parameters and in vitro drug release studies. Dissolution tests were performed using the USP type I basket method at 50 rpm in 6.8 phosphate buffer. From the in vitro dissolution studies it was found that by increasing the amount of polymers, release rate was decreased. Here, 100 mg of HPMC K100M showed 80% drug release in 8 hours whereas 120 mg showed 78.87% drug release in 10 hours. Similar decrease in the release rates were found with the increase of other polymers used in this study. The release data was fitted to various mathematical models such as zero order, first order, Higuchi, Korsmeyer Peppas and Hixson Crowell cube root law. The drug release follows mixed order kinetics and mechanism was found to be non-Fickian diffusion. Bangladesh Pharmaceutical Journal 18(1): 66-71, 2015